Evaluation of bone mineral density and bone turnover in children on anticoagulation - Thom, Katharina; Patsch, Janina Maria; Haufler, Florentina; Pees, Christiane; Albinni, Sulaima; Weber, Michael; Male, Christoph; Raimann, Adalbert (Frontiers in Endocrinology, 2023)
Background: Childhood and adolescence are critical periods of bone mineral acquisition. Children on anticoagulation (AC) might have an increased risk for reduced bone mineral density (BMD). Risk factors for impaired bone accumulation include chronic diseases, immobility, and medication. Vitamin-K (VK) deficiency reflected by undercarboxylated osteocalcin levels (ucOC) has been identified as predictor of osteoporosis and fractures. Data on bone health in children under AC are sparse.To evaluate BMD in children on AC, and to characterize risk factors of low BMD including VK and Vitamin D (VD) status.Methods: Single center, cross-sectional study of clinical-, biochemical-, and densitometric parameters. Assessment of VK surrogate parameters included ucOC and Matrix Gla protein (MGP).Results: 39 children (4-18 years; 12 females) receiving AC were included, 31 (79%) on VK antagonists, 8 (21%) on direct oral anticoagulants. Overall BMD was decreased for both lumbar spine (LS; -0.7SDS) and total body less head (TBLH; -1.32SDS) compared to pediatric reference data. Significant associations were found between early pubertal development and TBLH-BMD, and between BMI and LS-BMD. VK surrogate parameters were highly related with patients' age and pubertal development. Neither serum parameters nor AC-related factors predicted BMD. VD deficiency was detected in 26% with lower values during puberty.Our data indicate BMD reduction in pediatric patients on AC. Whilst AC-related factors were not predicting reduced BMD, low BMI and pubertal stages represented important risk factors. Awareness of risk factors for low BMD and high prevalence of VD deficiency during puberty could contribute to improve bone health in this vulnerable patient group.